Synthesis of Highly Uniform Molybdenum–Glycerate Spheres and Their Conversion into Hierarchical MoS2 Hollow Nanospheres for Lithium‐Ion Batteries. Issue 26 (20th April 2016) - Wang, Yawen; Yu, Le; Lou, Xiong Wen (David)
Abstract: Highly uniform Mo–glycerate solid spheres are synthesized for the first time through a solvothermal process. The size of these Mo–glycerate spheres can be easily controlled in the range of 400–1000 nm by varying the water content in the mixed solvent. As a precursor, these Mo–glycerate solid spheres can be converted into hierarchical MoS2 hollow nanospheres through a subsequent sulfidation reaction. Owing to the unique ultrathin subunits and hollow interior, the as‐prepared MoS2 hollow nanospheres exhibit appealing performance as the anode material for lithium‐ion batteries. Impressively, these hierarchical structures deliver a high capacity of about 1100 mAh g −1 at 0.5 A g −1 with good rate retention and long cycle life. Abstract : Dr Mo : Hierarchical MoS2 hollow nanospheres are synthesized with a self‐templating method from highly uniform Mo–glycerate solid spheres. By sulfidation and annealing, these Mo–glycerate solid spheres can be converted into hierarchical MoS2 hollow nanospheres. Owing to their unique structures, the hierarchical nanospheres show enhanced electrochemical properties as the anode material for lithium‐ion batteries.